Lycophyte plastid genomics: extreme variation in GC, gene and intron content and multiple inversions between a direct and inverted orientation of the rRNA repeat. Issue 2 (24th January 2019) - Mower, Jeffrey P.; Ma, Peng‐Fei; Grewe, Felix; Taylor, Alex; Michael, Todd P.; VanBuren, Robert; Qiu, Yin‐Long
Summary: Lycophytes are a key group for understanding vascular plant evolution. Lycophyte plastomes are highly distinct, indicating a dynamic evolutionary history, but detailed evaluation is hindered by the limited availability of sequences. Eight diverse plastomes were sequenced to assess variation in structure and functional content across lycophytes. Lycopodiaceae plastomes have remained largely unchanged compared with the common ancestor of land plants, whereas plastome evolution in Isoetes and especially Selaginella is highly dynamic. Selaginella plastomes have the highest GC content and fewest genes and introns of any photosynthetic land plant. Uniquely, the canonical inverted repeat was converted into a direct repeat (DR) via large‐scale inversion in some Selaginella species. Ancestral reconstruction identified additional putative transitions between an inverted and DR orientation in Selaginella and Isoetes plastomes. A DR orientation does not disrupt the activity of copy‐dependent repair to suppress substitution rates within repeats. Lycophyte plastomes include the most archaic examples among vascular plants and the most reconfigured among land plants. These evolutionary trends correlate with the mitochondrial genome, suggesting shared underlying mechanisms. Copy‐dependent repair for DR‐localized genes indicates that recombination and gene conversion are not inhibited by the DR orientation. Gene relocation in lycophyte plastomes occurs via overlapping inversions rather than transposase/recombinase‐mediated processes.